Poland's national and EU agricultural budget after 2015. Reduction in expenditures and directions of change = Krajowy i unijny budżet rolny Polski po 2015 r. Redukcja wydatków i kierunki zmian - Czyżewski, Andrzej; Matuszczak, Anna (Zielona Góra: Faculty of Economics and Management Press)
The aim of the article was to present changes which took place in the financing of the agricultural sector in Poland after 2015, i.e. from the moment when a new economic option started to emerge in the national economic policy. A transition from the pro-liberal to the pro-social option is noticeable, which is reflected in the restrictions on expenditures in the national agricultural budget.
Keywords: krajowe wydatki budżetowe; wydatki UE; sektor rolny; racjonalizacja budżetu; national budget expenditure; EU expenditure; agricultural sector